2007
DOI: 10.1152/ajplung.00089.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet-activating factor in pulmonary vascular remodeling associated with chronic high altitude hypoxia in ovine fetal lambs

Abstract: Platelet-activating factor (PAF) is implicated in pathogenesis of chronic hypoxia-induced pulmonary hypertension in some animal models and in neonates. Effects of chronic hypoxia on PAF receptor (PAF-R) system in fetal pulmonary vasculature are unknown. We investigated the effect of chronic high altitude hypoxia (HAH) in fetal lambs [pregnant ewes were kept at 3,801 m (12,470 ft) altitude from approximately 35 to 145 days gestation] on PAF-R-mediated effects in the pulmonary vasculature. Age-matched controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 39 publications
7
40
0
Order By: Relevance
“…3 Other studies have shown effects of hypoxia on nitric oxide mediated reactivity of intrapulmonary veins and arteries 9,10,11 or on remodeling of intrapulmonary vessels. 12,13 Following the observation of Murata et al, (2001) 1 which suggests a stronger effect of hypoxia on vascular remodeling than on nitric oxide mediated vascular reactivity of intrapulmonary vessels, the present study reveals that pathological changes beyond the intrapulmonary vessels, at the extreme end of the pulmonary or bronchiolar trees and alveolar regions, may also be a major cause of disease induced by chronic hypoxia. …”
Section: Discussionsupporting
confidence: 74%
“…3 Other studies have shown effects of hypoxia on nitric oxide mediated reactivity of intrapulmonary veins and arteries 9,10,11 or on remodeling of intrapulmonary vessels. 12,13 Following the observation of Murata et al, (2001) 1 which suggests a stronger effect of hypoxia on vascular remodeling than on nitric oxide mediated vascular reactivity of intrapulmonary vessels, the present study reveals that pathological changes beyond the intrapulmonary vessels, at the extreme end of the pulmonary or bronchiolar trees and alveolar regions, may also be a major cause of disease induced by chronic hypoxia. …”
Section: Discussionsupporting
confidence: 74%
“…NO acts on nearby smooth muscle cells to cause downstream stimulation of soluble guanylate cyclase (sGC) pathways that leads to vasorelaxation (3,45). Previous studies have shown that regulation of vessel relaxation through various receptor signaling systems is altered during pre-and postnatal development, as well as following prenatal chronic hypoxia, which imposes a significant stress on the fetus (9,10,35). Evidence suggests that acetylcholine (ACh)-dependent endothelium-mediated relaxation of the pulmonary vasculature is reduced in the fetus relative to the adult (57).…”
mentioning
confidence: 99%
“…These findings suggest that EGFR plays a role in fetal ovine pulmonary vascular remodeling following long-term HAH and that inhibition of EGFR signaling may reverse high altitude-induced pulmonary vascular remodeling. Similar to EGFR, platelet-activating factor (PAF) and PAF receptor have also been implicated in the pathogenesis of long-term HAH-induced pulmonary remodeling and hypertension in different animal models [56,57]. In those studies, high PAF and PAF receptor expression levels in the pulmonary arteries have been reported in the long-term hypoxia-exposed animals [56,57].…”
Section: Pulmonary Vascular Systemmentioning
confidence: 98%
“…Similar to EGFR, platelet-activating factor (PAF) and PAF receptor have also been implicated in the pathogenesis of long-term HAH-induced pulmonary remodeling and hypertension in different animal models [56,57]. In those studies, high PAF and PAF receptor expression levels in the pulmonary arteries have been reported in the long-term hypoxia-exposed animals [56,57]. Furthermore, PAF receptor antagonists attenuated hypoxia-induced pulmonary hypertension and pulmonary vascular remodeling [56], suggesting that PAF receptor-mediated signaling also plays a key role in pulmonary vascular remodeling.…”
Section: Pulmonary Vascular Systemmentioning
confidence: 99%